PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MELALUI PENDEKATAN PEMBELAJARAN BERDIFERENSIASI TERINTEGRASI DISCOVERY LEARNING KELAS IV DI SD N GENDONGAN 01 SALATIGA - Lidya Dinda Widhi Hapsari; Krisma Widi Wardani; Deta Maria Sri Darta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was prompted by observations of the potential for enhancing thisability among fourth-grade students at SD Gendongan 01 Salatiga. The objectiveof this classroom action research (CAR) was to improve students' creative thinkingability through the application of a differentiated learning approach integrated withthe Discovery Learning model. The study employed a CAR design implemented intwo cycles with [19] students. The action research learning integrating theDiscovery Learning syntax with strategies for process and product differentiation.Data were collected through observation, creative thinking tests, and productassessment, then analyzed quantitatively and qualitatively. The results showed asignificant improvement in students' creative thinking ability. At the end of Cycle 1,the distribution of creativity levels was: 36.8% highly creative, 47.4% creative, and15.8% sufficiently creative. Following refinements to the intervention, Cycle 2results showed 63.2% highly creative and 36.8% creative, with no studentsremaining in the sufficiently creative category. This improvement indicated thatDiscovery Learning provides an effective exploratory framework when combinedwith differentiation that accommodates individual needs through process andproduct adjustments. It was concluded that the integration of differentiated learningand Discovery Learning effectively enhances the creative thinking ability of fourth-grade students at SD Gendongan 01 Salatiga.